Pablo Aparicio Resco. Entre Aidós Y Peitho. La iconografía del gesto del velo en la Antigua Grecia - Llewellyn-Jones, Lloyd (Journal of Greek Archaeology, 2016)
The subject of Pablo Resco’s neat and useful study is the artistic development and cultural meaning of the ‘veil-gesture’ in Greek art. The ‘veil-gesture’, as I named it back in 2003 in my monograph Aphrodite’s Tortoise: the veiled woman of ancient Greece (Swansea: Classical Press of Wales), is one of the most frequently encountered motifs in Greek art. In fact, there are so many examples that a close study of the motif was well beyond the limits of my work at that time. Resco, drawing closely on Aphrodite’s Tortoise, has taken the opportunity to expand the investigation of the repertoire of the motif.